Inside Fatima ; Breaking up is hard to do ; Sakay the movie [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Exposes the alledged irregularities of Fatima administration through silhoutte interview with students. Deals with legal annulments & marital break-ups. The making of Sakay, the movie with Raymond Red as film director.
Inside Fatima (17 min.) -- Breaking up is hard to do (19 min.) -- Sakay: the movie (19 min.)
VHS.
Keywords: Our Lady of Fatima College Anomaly, 1993.; Marriage -- Annulment (Canon Law) -- Philippines; Cinematography -- Philippines; Motion pictures -- Production and direction. -- Philippines